Poly(2‐ethyl‐2‐oxazoline) Featuring a Central Amino Moiety. Issue 13 (7th May 2021) - Dirauf, Michael; Fritz, Nicole; Gottschaldt, Michael; Weber, Christine; Schubert, Ulrich S.
Abstract: The incorporation of an amino group into a bifunctional initiator for the cationic ring‐opening polymerization (CROP) is achieved in a two‐step reaction. Detailed kinetic studies using 2‐ethyl‐2‐oxazoline demonstrate the initiators' eligibility for the CROP yielding well‐defined polymers featuring molar masses of about 2000 g mol –1 . Deprotection of the phthalimide moiety subsequent to polymerization enables the introduction of a cyclooctyne group in central position of the polymer which is further exploited in a strain‐promoted alkyne‐azide click reaction (SpAAC) with a Fmoc‐protected azido lysine representing a commonly used binding motif for site specific polymer–protein/peptide conjugation. In‐depth characterization via electrospray ionization mass spectrometry (ESI) confirms the success of all post polymerization modification steps. Abstract : A new bifunctional initiator for the cationic ring‐opening polymerization of 2‐ethyl‐2‐oxazoline is presented. The incorporation of an amino moiety in central position is achieved through a phthalimide as a protective group. Kinetic studies confirm a living polymerization character with pseudo first‐order kinetics. Post polymerization modifications demonstrate the eligibility of selective central functionalization of the polymer.